Evaluation of Cell Permeability Characteristics and Damage during Natural Evaporation of Cryoprotectant-Loaded Microdroplets - Liu Linfeng; Cui Mengdong; Zhan Taijie; He Wei; Xu Yi (Zhileng xuebao)
Natural evaporation of microdroplets was studied as a new method for the addition of cryoprotectants. The effects of the initial volume and concentration on cell permeation characteristics and damage during cryoprotectant loading by natural evaporation of microdroplets were investigated systematically using image processing techniques. Combined with theoretical analysis of cell permeation and damage models, the results were compared with traditional cryoprotectant loading methods (one-step and two-step loading). The results show that, the faster the evaporation rate, the easier it was for the cryoprotectant to achieve the required concentration, which could reduce the loading time (by 4907 s for 1 μL compared with 5 μL).?As the initial concentration of the protectant decreased, the loading time increased gradually (2460 and 1346 s for 0.5 and 2.5 M, respectively); however, the cell volume change caused by extremes was significantly reduced (14% and 43% of the initial volume for 0.5 and 2.5 M, respectively), as was the cumulative toxic damage (23.05 and 47.53 for 0.5 and 2.5 M, respectively). Compared with the usual loading approach, microdroplet loading by natural evaporation considerably enhanced cell survival and proliferation (P< 0.05). Cell survival was 96.73% ± 0.54%, a 16% increase over one-step loading, and cell wall adherence was considerably better at 48 h than that with two-step loading. This innovative technique substantially reduced cell damage while simplifying the cryoprotectant loading process.